Free spectral range, and coupling coefficient analysis of integrated fano resonance in all-pass micro-resonator - Hairol Aman, Mohammad Amirul; Ahmad Noorden, Ahmad Fakhrurrazi; Ahmad Fajri, Faris Azim; Abdul Hamid, Ahmad Noor; Daud, Suzairi (Springer Science and Business Media Deutschland GmbH, 2022)
We demonstrate the simulation for all-pass microring resonators with integrated Fano resonance to obtain high Free Spectral Range (FSR). The simulation mainly performed to generate high FSR by varying 2 parameters that affect the system which are radius of the ring and distance between end-facet. Furthermore, the analysis is proceeded by a variation of coupling coefficient. The impact to the output spectrum due to variations of the parameters was observed and analyzed, focusing on the FSR. We also investigate the effect of coupling coefficient variation and its contribution to the optical performance of the microring. The highest FSR obtained from this simulation was 273.752 nm.